2009
DOI: 10.1080/15257770903044523
|View full text |Cite
|
Sign up to set email alerts
|

Thiophosphate Analogs of c-di-GMP: Impact on Polymorphism

Abstract: Seven phosphorothioate analogs of c-di-GMP (all diastereomers of mono-, di-, and trithiophosphates) were prepared to assess the impact of the thioate substitutions on c-di-GMP polymorphism using 1D 1 H and 31 P NMR, along with 2D NOESY and DOSY, for both the Na + and K + salts. The K + salts display more extensive higher order complex formation than the Na + salts, resulting primarily in octamolecular complexes with K + , but tetramolecular complexes with Na + . Further, the presence of one or two [S P ] sulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 41 publications
3
28
1
Order By: Relevance
“…We identified this peak as c-(S p S p )-di-G ps because the molecule had an m/z value of 721 like the other two c-di-GMP diphosphorothioates and because the retention time was in between that of c-di-GMP and c-(R p S p )-di-G ps . This same order of elution was previously reported for the three c-di-GMP diphosphorothioate stereoisomers ( 55 ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We identified this peak as c-(S p S p )-di-G ps because the molecule had an m/z value of 721 like the other two c-di-GMP diphosphorothioates and because the retention time was in between that of c-di-GMP and c-(R p S p )-di-G ps . This same order of elution was previously reported for the three c-di-GMP diphosphorothioate stereoisomers ( 55 ).…”
Section: Resultssupporting
confidence: 86%
“…However, this method only allows synthesis of R p R p and R p S p phosphorothioate cyclic dinucleotides. A more complicated synthetic procedure, requiring additional purification steps, is necessary to prepare the S p S p phosphorothioate ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, as a phosphate triester cyclization does not lend itself to the preparation of thiophosphates, prior to our recent work16 only the analog with a single thiophosphate had been reported 8,13. We have recently prepared and characterized all of the thiophosphate diastereomers of c-di-GMP containing one, two, or three sulfur atoms,16 but in such modest yields that opportunities for further study are limited, beyond confirming that they showed similar polymorphism to that we had found for c-di-GMP itself 17. Thiophosphate analogs of defined stereochemistry are of particular interest as probes of phosphate/metal interaction, and because of the resistance of thiophosphates to enzymatic hydrolysis.…”
mentioning
confidence: 99%
“…Mono and dithiophosphate analogs were synthesized in solution as previously described 35 . The absolute stereochemistry of the thiophosphate c-di-GMP analogs was assigned as previously described based on the specificity of P1 and venom phosphodiesterases 36 . 3′- phosphate CPG beads, guanosine methylphosphonamidite precursors, and Poly-Pak II desalting columns were purchased from Glen Research.…”
Section: Methodsmentioning
confidence: 99%